Pregnancy and neonatal outcomes in women with HIV-1 exposed to integrase inhibitors, protease inhibitors and non-nucleoside reverse transcriptase inhibitors: an observational study - Floridia, Marco; Dalzero, Serena; Giacomet, Vania; Tamburrini, Enrica; Masuelli, Giulia; Savasi, Valeria; Spinillo, Arsenio; Tassis, Beatrice; Franceschetti, Laura; Degli Antoni, Anna Maria; Sansone, Matilde; Guaraldi, Giovanni; et al. (Infection, 2020)
Purpose Recommended regimens for pregnant women with HIV-1 are composed of two nucleoside reverse transcriptase inhibitors (NRTI) plus either a ritonavir-boosted protease inhibitor (PI) or an integrase strand transfer inhibitor (ISTI), with non-nucleoside reverse transcriptase inhibitors (NNRTI) representing an alternative drug class. The study’s purpose was to compare these three options in terms of pregnancy outcomes. Methods Data from a national observational study of pregnant women with HIV-1 were used. The analysis included all pregnancies reported between 2008 and 2018, ending in live births and exposed within 32 weeks of gestation to three-drug regimens composed of a NRTI backbone plus a PI, a NNRTI or a ISTI, without class switching during pregnancy. Clinical and laboratory outcomes were evaluated in univariate and multivariable analyses. Results Overall, 794 exposed pregnancies were analyzed (PI 78.4%, NNRTI 15.4%, ISTI 6.2%). Almost all outcomes had similar rates in the three groups. Women who received PI in pregnancy were less likely to be virologically suppressed at third trimester. PI use was associated with higher bilirubin and triglyceride levels, and ISTI use with a lower rate of low birthweight. The differences in viral suppression at third trimester and in low birthweight were not maintained in multivariable analyses that were adjusted for confounders. Discussion We found no major differences in a wide range of outcomes relevant for pregnant women with HIV. Such results are reassuring, and this information may be helpful in a context of preconception counseling when therapeutic choices for pregnancy are discussed between women and care providers.